FOXS1 Promotes Tumor Progression by Upregulating CXCL8 in Colorectal Cancer - Qiu, Junfeng; Li, Mingzhou; Su, Cailin; Liang, Yihao; Ou, Ruizhang; Chen, Xiaoning; Huang, Chengmei; Zhang, Yaxin; Ye, Yaping; Liao, Wenting; Zhang, Chao (Frontiers in Oncology, 2022)
Background: Forkhead Box S1 (FOXS1) is a member of the Forkhead box (FOX) transcriptional factor superfamily. The biological roles and underlying regulatory mechanism of FOXS1 in CRC remain unclear. Methods: Bioinformatics analysis, western blotting, real-time PCR, and immunohistochemistry (IHC) were used to detect the expression FOXS1 in CRC. MTT assay, Transwell assay, human umbilical vein endothelial cells tube formation assay, and chicken chorioallantoic membrane assay were performed to investigate the effects of FOXS1 on proliferation, invasion, and angiogenesis. Additionally, tumor formation assays and orthotopic implantation assay were used to investigate the effects of FOXS1 on tumor growth and metastasis in vivo. Furthermore, gene set enrichment analysis (GSEA) was used to analysis the correlation between FOXS1 and and EMT or angiogenesis. The correlation between FOXS1 and CXCL8 expression were analysis in clinical CRC samples using IHC. Results: The results showed that FOXS1 expression was upregulated in CRC tissues compared with adjacent normal intestine tissues. High FOXS1 expression is positively correlated with poor survival. FOXS1 promoted malignant behavior of CRC cancer cells in vitro, including proliferation, invasion, and angiogenesis. In addition, FOXS1 promoted tumor growth and metastasis in nude mice. Mechanistically, FOXS1 upregulated the expression of C-X-C motif chemokine ligand 8 (CXCL8) at the transcriptional level. Knockdown of CXCL8 blocked FOXS1-induced enhancement of the EMT and angiogenesis. GSEA analyses in public CRC datasets revealed strong correlations between FOXS1 expression and EMT marker and angiogenesis markers. IHC showed that FOXS1 expression was positively correlation with CXCL8 expression and CD31 expression in clinical CRC samples. Conclusion: The results suggest that FOXS1 promotes angiogenesis and metastasis by upregulating CXCL8 in CRC. Interference with the FOXS1/CXCL8 axis may serve as a potential therapeutic target for the treatment of metastatic CRC.